Effects of ozone-treated domestic sludge on hydroponic lettuce growth and nutrition - Peng YANG; Yan-zhi GUO; Ling QIU (Journal of Integrative Agriculture, 2018)
Here, the ozone-treated domestic sludge was diluted up to four different multiples and utilized as a nutritional source for hydroponic lettuce growth. Additionally, lettuce was cultured using the modified Hoagland nutrient solution as a control. The effects of ozone-treated domestic sludge on lettuce growth and nutrition were studied. Results showed that the lettuce treated with modified Hoagland inorganic nutrient solution had increased leaf number, plant height, fresh weight and dry weight compared to those treated with the ozone-treated domestic sludge dilution (P<0.05). However, the lettuce cultivated with the 2-fold ozone-treated sludge dilution showed significantly higher (P<0.05) contents of chlorophyll, soluble sugar and ascorbic acid (Vc) compared to that treated with modified Hoagland nutrient solution. And the nitrate concentration in the lettuce cultured with the 2-fold ozone-treated sludge dilution was 53.93% less than that cultured with the modified Hoagland nutrient solution, which was a significant improvement (P<0.05). This study suggested that the 2-fold ozone-treated sludge dilution is optimal for lettuce hydroponic nutrient requirements.